Diagnosis of Flexible Pavement Road Deterioration By Using ExpertSystem - A. Awad, Hamed; A. Mansour Al-Kubaisy, Yousif; Sagheer, AliM. (Iraqi Journal of Civil Engineering, 2008)
AbstractDuring the last four decades, incidence of failure of flexible pavement road has been seenwidely for many reasons, such as increasing service axial loads, repetition of traffic loadsand the environmental effects. An expert systemis an interactive computer-based decisiontool that uses both facts and heuristics to solve difficult decision problems based onknowledge acquired from an expert. To realize these requirements, a logic programmingProlog language was utilized together with diagnosis technology. The logic programminglanguage formalizes the domain knowledge. The expert system Diagnosis of FlexiblePavement Road Deterioration (DFPRD) developed in this paper is a diagnostic advisorysystem, which can be used as an alternative to the human expert, to give technicaldecisions in diagnosing deterioration in flexible pavement.Keywords: Expert System, Pavement Road Deterioration